2020
DOI: 10.3390/ijerph17186807
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ and Young Adult Non-Smokers’ Perceptions and Perceived Impact of Snus and E-Cigarette Modified Risk Messages

Abstract: Although no tobacco products are safe, tobacco companies in the United States may request regulatory authorization to make certain “modified risk tobacco product” (MRTP) claims in their marketing. However, few qualitative studies have explored consumer perceptions and understanding of comparative risk messages and wordings. We examined consumer perceptions of statements indicating reduced risks and exposure to chemicals from snus and e-cigarettes relative to smoking. We conducted 12 focus groups with adult smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“… 14 In light of the EVALI outbreak, studies have begun describing the likely influence of the lung disease and EVALI-related news on risk perceptions. 8 , 18 , 19 For example, one qualitative study found that exposure to EVALI news was associated with reduced interest in e-cigarettes among young adult non-smokers (a potentially unintended positive effect) but was also associated with increased harm perceptions and reduced receptivity to switching to e-cigarettes among adult current smokers (a potentially negative unintended effect). 19 Population-level research has also suggested increases in perceptions that e-cigarettes are equally or more harmful than traditional cigarettes after EVALI, 8 even outside of the United States.…”
Section: Discussionmentioning
confidence: 99%
“… 14 In light of the EVALI outbreak, studies have begun describing the likely influence of the lung disease and EVALI-related news on risk perceptions. 8 , 18 , 19 For example, one qualitative study found that exposure to EVALI news was associated with reduced interest in e-cigarettes among young adult non-smokers (a potentially unintended positive effect) but was also associated with increased harm perceptions and reduced receptivity to switching to e-cigarettes among adult current smokers (a potentially negative unintended effect). 19 Population-level research has also suggested increases in perceptions that e-cigarettes are equally or more harmful than traditional cigarettes after EVALI, 8 even outside of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they wanted to stop smoking or at least to decrease the amount of combustible cigarette consumption, but they also wanted to continue smoking with less harmful product. This conflicting attitude of e-cigarette users explains why they are easily exploited by manufactures who claim e-cigarettes are MRTPs 17 . In addition, e-smokers were more susceptible to stress than non-smokers or smoker.…”
Section: Discussionmentioning
confidence: 99%
“…Data are from 11 focus groups from a broader study on MRTP claim reactions ( Wackowski et al, 2020 , Wackowski et al, 2021 ). Six groups focused on snus messages and five on e-cigarette messages 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Messages were informed by previous studies and MRTP applications. Details about those messages, procedures and findings are presented elsewhere ( Wackowski et al, 2020 , Wackowski et al, 2021 ). Briefly, although some smokers expressed interest in MRTP statements/products, participants also expressed considerable message skepticism.…”
Section: Methodsmentioning
confidence: 99%